A Narrative Review of Medetomidine Toxicity: an Update for Emergency Medicine - Anthony Spadaro; Erin D. Wieruszewski; Brandy N. Hernandez; Brandon M. Carius; Brit Long (Current Emergency and Hospital Medicine Reports, 2026)
Abstract Purpose of Review Unregulated opioids often contain various adulterants, such as alpha-2 agonists, benzodiazepines, and stimulants. Medetomidine, an alpha-2 agonist, has emerged in the United States and has been linked to significant toxicity and severe withdrawal symptoms. This narrative review reviews medetomidine toxicity and withdrawal with a focus on management in the acute care setting. Recent Findings There is significant regional variation in the prevalence of secondarily added adulterants, and regions of the Northeast United States are experiencing high prevalence of medetomidine adulteration. Medetomidine exposure is associated with hypotension, bradycardia, and profound sedation. Naloxone will only reverse respiratory depression from concomitant opioid use without affecting the toxicity of medetomidine, making management largely supportive. Chronic exposure to medetomidine can lead to withdrawal with discontinued use. Patients with medetomidine withdrawal can be critically ill due to a catecholamine surge and sympathetic hyperactivity. Signs and symptoms begin within 6–24 h of last use, often before opioid withdrawal develops, typically with hypertension, tachycardia, anxiety, tremor, diaphoresis, nausea, vomiting, and hypoactive delirium. Treatment for medetomidine withdrawal includes alpha-2 agonists such as clonidine, guanfacine, tizanidine, or dexmedetomidine and antiemetics. Summary Patients with opioid use disorder may be exposed to medetomidine as an adulterant which can cause severe illness in overdose and withdrawal. Patients in withdrawal should be treated with alpha-2 agonists and may require hospital admission, including to a critical care setting for severe withdrawal, and concomitant opioid withdrawal may be treated with agents such as buprenorphine or methadone.